Evaluation of a non-mydriatic camera in Indian and European diabetic patients. Issue 11 (November 1988) - Mohan, R; Kohner, E M; Aldington, S J; Nijhar, I; Mohan, V; Mather, H M
Abstract : The value of the Canon CR3-45NM non-mydriatic fundus camera in screening for diabetic retinopathy has been assessed in two ethnic groups, namely, 45 Indian and 40 European diabetic patients. There was 72% agreement between ophthalmoscopy by an ophthalmologist and the photographic assessment, and 100% agreement on clinically important lesions requiring treatment. However, peripheral retinal lesions, seen on ophthalmoscopy but lying outside the photographic field, occurred in 4% of eyes. 6% of photographs were totally unassessable and an additional 12% were only partially assessable. The prevalence and severity of retinopathy was similar in Indian and European patients. The advantages and disadvantages of the non-mydriatic camera in screening for diabetic retinopathy are discussed.